NEW CULTIVAR OF SOFT WINTER WHEAT ‘BEREZIT’ - N. M. Komarov; N. I. Sokolenko; N. L. Zobnina; S. A. Kazachkov (Зерновое хозяйство России, 2018)
New cultivar of soft winter wheat ‘Berezit’ has been described in the article. The cultivar is a middle-late maturing one with a set of unique characteristics. It possesses a complex immunity to leaf-stem diseases widely spread in the region and doesn’t need any fungicide treatment during vegetation period. The variety possesses higher salt tolerance than a standard one ‘Stepnaya 7’ well-known in the area.